THE EFFECT OF CLASSICAL MUSIC THERAPY ON REDUCING STRESS LEVELS IN STUDENTS AHEAD OF EXAMS AT THE COLLEGE OF HEALTH SCIENCE OF HUSADA JOMBANG - Talapessy, Yana; Rustanti, Elly; Darsini, Darsini; Zatihulwani, Eliza Zihni (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2025)
individual's cognition and affect physical, emotional, and behavioral. Objectives: The purpose of this study is to determine the effect of providing classical music therapy on reducing stress levels in students ahead of exams at the College of Health Science of Husada Jombang. Methods: This study uses a pre-experimental design with a one-group pretest-posttest design approach. In this study, a population of 117 respondents who experienced stress before the exam at the College of Health Science of Husada Jombang was obtained with a sample of 44 respondents, and a simple random sampling technique. The measurement tool uses an SLSI (student life stress inventory) questionnaire and is tested with the Wilcoxon signed rank test. Results: The results of the study conducted on students before the exam with the level of stress at College of Health Science of Husada Jombang showed that the results of the Pre-test of classical music therapy were obtained Most of the moderate stress, namely 23 respondents (52.3%), while the results of the post-test of classical music therapy became almost all low stress, namely 36 respondents (81.8%). Based on the results of the statistical test using the Wilcoxon signed rank test, results were obtained with a significance value of p value = 0.000 < 0.05, H0 rejected and H1 accepted, which means that there is an effect of providing classical music therapy on reducing stress levels in students ahead of the exam at the College of Health Science of Husada Jombang. Conclusion: It can be concluded that classical music therapy is given to students before exams and is used as an alternative to reduce stress levels in students. It is hoped that by providing classical music therapy, it can be used to reduce stress levels for respondents and can research into mental health. Gain a deeper understanding of the effects of classical music therapy in reducing stress, as well as gain experience and references for further research.